School Management System: Human Resource (With Web-Based): Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Human Resource Management faces the following challenges: a lack of an operationalsystem. Because the School Management System Human Resources is not properlymanaged, it may supply incorrect information, causing increasing challenges in dealing withstaff. Poor staff retention techniques. The lack of a good management strategy reduces theorganization's quality, which leads to employee exit and transfer to other firms. Lack of qualityin recruiting, as well as inadequate recruitment strategy formulation, contribute to ignoringtalented and knowledgeable job seekers. It is extremely difficult for the human resourcesdepartment to communicate with other departments that are looking for new hires because ofthe department's poor administration and slow system.The Human Resource Management System project will better deliver the information that HRpersonnel and school employees require. Every response offered to individuals participatingin the School Management System Human Resources will be better structured and faster.Creating a strategy to acquire new personnel for the department and an efficient hiringprocedure for talented individuals. Finding new workers with the appropriate talent will beeasier with School Management, and every employee will receive the training they need tostay in their designated area.Maintaining a record of each employee's information across the company is made simple byhuman resource management. The ability to oversee a more thorough human resourcemanagement strategy by being up to date on how each change inside the organization affectseach employee. The system will aid the Department in maintaining and adhering to theStandard Operating Procedures when the head and staff of Human Resources need to turnover data, processes, and records in a hassle-free manner. It will also provide the bestcommunication for a faster transaction without even needing more people to be involved. Asecure database will be made available by the system to house files, data, and informationthat will be used for a long period.
Keywords: IT & Management